Comparison of Treadmill Trip-Like Training Versus Tai Chi to Improve Reactive Balance Among Independent Older Adult Residents of Senior Housing: A Pilot Controlled Trial. (21st December 2018) - Aviles, Jessica; Allin, Leigh J; Alexander, Neil B; Van Mullekom, Jennifer; Nussbaum, Maury A; Madigan, Michael L
Abstract: Background: There is growing interest in using perturbation-based balance training to improve the reactive response to common perturbations (eg, tripping and slipping). The goal of this study was to compare the efficacy of treadmill-based reactive balance training versus Tai Chi performed at, and among independent residents of, older adult senior housing. Methods: Thirty-five residents from five senior housing facilities were allocated to either treadmill-based reactive balance training or Tai Chi training. Both interventions were performed three times per week for 4 weeks, with each session lasting approximately 30 minutes. A battery of balance tests was performed at baseline, and again 1 week, 1 month, 3 months, and 6 months post-training. The battery included six standard clinical tests of balance and mobility, and a test of reactive balance performance. Results: At baseline, no significant between-group differences were found for any balance tests. After training, reactive balance training participants had better reactive balance than Tai Chi participants. Maximum trunk angle was 13.5° smaller among reactive balance training participants 1 week after training ( p = .01), and a reactive balance rating was 24%–31% higher among reactive balance training participants 1 week to 6 months after training ( p < .03). Clinical tests showed minimal differences between groups at any time point after training. Conclusion: Trip-like reactive balance training performed at senior housing facilities resulted in better rapid balance responses compared with Tai Chi training.